Complexos fosfínicos de rutênio contendo os ligantes nitro, nitrosilo ou piridinas, com atividades antitumorais e antituberculose - Cruz Júnior, José Wilmo da (2010)
In this work, a series of cis-[RuCl(L)(dppb)(5-mebipy)]PF6 (L=pyridine, 4- metylpyridine, 4-phenylpyridine, 4-vinylpyridine, 4-terc-butylpyridine and 4- aminopyridine); the cis-[RuCl(NO2)(dppb)(5-mebipy)], the cis-[Ru(NO2)2(dppb)(5- mebipy)], the ct-[RuCl(NO)(dppb)(5-mebipy)](PF6)2, and the cc- [RuCl(CH3CN)(dppb)(5-mebipy)]PF6 [dppb = 1,4-bis(diphenylphosphino)butane and 5-mebipy = 5,5´-dimetyl-2,2´-bipyridine] were synthesized and characterized by means of elemental analysis, IR/UV/Vis spectroscopies, cyclic voltammetry, pulse differential voltammetry, NMR 31P{1H}, molar conductivity, and when was the case, by X-ray crystallography. It was showed that for the cis-[RuCl(L)(dppb)(5-mebipy)]PF6 complexes the E1/2 values decrease with the increase of the pKa of the L ligand. For the cis- [RuCl(NO2)(dppb)(5-mebipy)] and cis-[Ru(NO2)2(dppb)(5-mebipy)] complexes, the IR data suggested that the NO2 - species are coordinated to the metal throughout the nitrogen forming nitro complexes. This was confirmed by the determination of the Xray structure of the cis-[Ru(NO2)2(dppb)(5-mebipy)] complex, in which, the nitrite ligands are coordinated to the ruthenium throughout the nitrogen. The electrolysis of the ct-[RuCl(NO)(dppb)(5-mebipy)](PF6)2 complex at 300 mV produces the ct-[RuCl(CH3CN)(dppb)(5-mebipy)]PF6 compound (CH3CN trans the phosphorus), which isomerizes to the cc-[RuCl(CH3CN)(dppb)(5-mebipy)]PF6 complex (CH3CN trans the nitrogen), the final product of the process. It was showed that these isomers are formed by the nitrosyl dissociation of the NO from the ct- [RuCl(NO)(dppb)(5-mebipy)](PF6)2 complex without any potential application. This process was followed by 31P{1H} experiments, in which both isomers were detected, and after a few minutes only the cc isomer was present in the solution. The biological assays showed that the complexes synthesized in this work are active against MDA-MB 231 and K-562 tumor cells and present anti-tuberculosis properties.